Variation of cholinesterase-based biosensor sensitivity to inhibition by organophosphate due to ionizing radiation - Pohanka, Miroslav; Koch, Miroslav (Sensors (Basel, Switzerland), 2009)
A cholinesterase based biosensor was constructed in order to assess the effects of ionizing radiation on exposed AChE. Although the primary objective of the experiment was to investigate the effect of ionizing radiation on the activity of the biosensor, no changes in cholinesterase activity were observed. Current provided by oxidation of thiocholine previously created from acetylthiocholine by enzyme catalyzed reaction was in a range 395-455 nA. No significant influence of radiation on AChE activity was found, despite the current variation. However, a surprising phenomenon was observed when a model organophosphate paraoxon was assayed. Irradiated biosensors seem to be more susceptible to the inhibitory effects of paraoxon. Control biosensors provided a 94 ± 5 nA current after exposure to 1 ppm paraoxon. The biosensors irradiated by a 5 kGy radiation dose and exposed to paraoxon provided a current of 49 ± 6 nA. Irradiation by doses ranging from 5 mGy to 100 kGy were investigated and the mentioned effect was confirmed at doses above 50 Gy. After the first promising experiments, biosensors irradiated by 5 kGy were used for calibration on paraoxon and compared with the control biosensors. Limits of detection 2.5 and 3.8 ppb were achieved for irradiated and non-irradiated biosensors respectively. The overall impact of this effect is discussed.
Keywords: organophosphate; cholinesterase; acetylcholinesterase; paraoxon; biosensor; radiation; nerve agents